ANALYSIS OF INDONESIAN CINNAMON EXPORT COMPETITIVENESS IN THE INTERNATIONAL MARKET - Nainggolan, Saidin; Saputra, Ardhiyan; Pratama, Agustynus (JALOW | Journal of Agribusiness and Local Wisdom, 2025)
This study aims to describe the development of cinnamon and analyze the competitiveness of Indonesian cinnamon exports in the international market. The method used is the Revealed Comparative Trade Advantage (RCTA) to analyze competitiveness in terms of comparative advantage, and the Export Competitiveness Index (XCi) to measure competitiveness in terms of competitive advantage to assess Indonesia's relative competitiveness compared to competing countries such as Sri Lanka, China, Vietnam, and Saudi Arabia. The data used is time series data from 2000 - 2022 from the Central Statistics Agency (BPS), the Food and Agriculture Organization (FAO), and trade reports from the World Trade Organization (WTO). The results of the analysis show that in terms of comparative advantage, Sri Lanka's RCTA value has the highest RCTA value (867.535), followed by Indonesia (21.815), Vietnam (18.663), China (1.507), and Saudi Arabia (-1.925). In terms of competitive advantage, the highest XCi value is held by Saudi Arabia (1.729), followed by Vietnam (1.096), China (1.024), Indonesia (1.008), and Sri Lanka (0.981). This finding shows that although Indonesia has a strong comparative advantage, its competitive advantage tends to be low. To increase competitiveness, a comprehensive strategy is needed to increase production efficiency, invest in post-harvest technology, and strengthen more proactive export policies.